How Community Pharmacists can help patients on Antidepressants at risk for suicides and sexual dysfunction - Salman, Saad; A, Abdullah; Idrees, Jawaria; Shah, Fahad Hassan (Journal of Pharmacy Practice and Community Medicine)
Widespread use of antidepressant drugs has led to suicidal attempts and sexual dysfunction among adolescent psychiatric patients.[1] Patients usually complain for delayed ejaculation and libido loss with SSRIs group specifically. [2] Although in premature ejaculation these drugs have significant impact, but still they are risky for many patients; if they are not well aware of the considerable side effects these drugs carry along. Adolescents are usually victimized by such side effects like suicidal intents, non-compliance, drug denial and this may ultimately result in behavioral disorders.[3] Educating the patient and his relatives regarding these potential side effectsis very necessary for the pharmacist.[4] The mortality rate of adolescents with depression is highly contributed by these side effects. The foremost culprit for adolescent mortality was tricyclic and SSRI’s use in the US.[2,4] So application of appropriate actions is need of the day while prescribing these drugs.[5-6]